Identification and Validation of DEPDC1B as an Independent Early Diagnostic and Prognostic Biomarker in Liver Hepatocellular Carcinoma - Fan, Xiaoyan; Wen, Junye; Bao, Lei; Gao, Fei; Li, You; He, Dongwei (Frontiers in Genetics, 2022)
Liver hepatocellular carcinoma (LIHC) is one of the most lethal tumors worldwide. Though the detail mechanism remains unclear, the early diagnosis of LIHC could significantly improve the 5-year survival of LIHC patients. Thus, it is important to explore novel molecular markers for early diagnosis and developing efficient therapies for LIHC patients. Recently, DEPDC1B have been reported to participate in regulating cell mitosis, transcription, and tumorigenesis. To explore the valuable diagnostic and prognostic markers for LIHC and further elucidate the mechanisms underlying DEPDC1B-related LIHC, kinds of databases, such as Oncomine, Gene Expression Profiling Interactive Analysis (GEPIA), UALCAN, Kaplan-Meier plotter and The Cancer Genome Atlas (TCGA), were interrogated to determine the association between DEPDC1B expression and prognosis in LIHC patients. Overall, DEPDC1B mRNA level was highly expressed in LIHC tissues, compared with that in normal tissues (p < 0.01). High DEPDC1B expression was associated with poor overall survival (OS) in LIHC patients, especially in stage II, IV and grade I, II, III patients (all p < 0.05). Univariate and multivariate Cox regression analysis showed that DEPDC1B was an independent risk factor for OS among LIHC patients (HR = 1.3, 95% CI: 1.08-1.6, p = 0.007). In addition, the protein expression of DEPDC1B was validated using Human Protein Atlas database. Furthermore, DEPDC1B expression was confirmed by Real-Time PCR using 5 pairs of matched LIHC tissues and their adjacent noncancerous tissues. KEGG pathway analysis indicated that high DEPDC1B expression may associate with several signaling pathways, such as MAPK signaling, regulation of actin cytoskeleton, p53 signaling, Wnt signaling pathways. Furthermore, high DEPDC1B expression may be deeply associated with various cancers. In conclusions, DEPDC1B maybe an independent risk factor for OS among LIHC cancer patients and may be used as an early diagnostic marker in patients with LIHC.